Management of patients with dry eye syndrome with systemic autoimmune and infectious diseases - G.M. Chernakova; E.A. Kleshcheva (РМЖ "Клиническая офтальмология")
Chernakova G.M.1, Kleshcheva E.A.2 1 S. Fyodorov Eye Microsurgery Federal State Institution, Moscow 2 Russian Medical Academy of Continuous Professional Education, Moscow It is known, that instability and hyperosmolarity of the tear film, inflammation and damage to the eye surface play a leading role in the pathogenesis of dry eye syndrome (DES), as well as neurosensory disorders. Multifactority of this pathology, along with poorly understood pathophysiology and the potential progressive nature of the course of the disease, limited range of diagnostic tests, creates difficulties in the diagnosis and treatment of DES. The article considers the features of the clinical course of DES against the background of systemic autoimmune and chronic infectious diseases. The review highlights the key aspects of pathogenesis and current therapy of DES in patients with rheumatoid arthritis, systemic lupus erythematosus, autoimmune thyroiditis, as well as in patients with HIV infection, viral hepatitis B and C, Epstein-Barr virus. The common pathogenetic processes of development of DES in patients with systemic infectious and non-infectious diseases allows to consider the reduction of oxidative stress as the main direction of the drug therapy. Undoubtedly, systemic therapy of the underlying disease is mandatory, however,  it is the ophthalmologist’s responsibility to identify symptoms of tear production decrease against the background of these diseases, to establish the severity of DES and to prescribe therapy that improves the quality of life of patients. Key words: dry eye syndrome, systemic autoimmune diseases, human immunodeficiency virus, hepatitis B virus, hepatitis C virus, Epstein-Barr virus, antioxidant therapy, Artelac Splash, Artelac Balance. For citation: Chernakova G.M., Kleshcheva E.A. Management of patients with dry eye syndrome with systemic autoimmune and infectious diseases. RMJ “Clinical ophthalmology”. 2018;2:–90.